Agronomic Biofortification of Wheat Through Proper Fertilizer Management to Alleviate Zinc Malnutrition: A Review. Issue 2 (19th January 2023) - Yadav, Arvind K.; Seth, Anindita; Kumar, Vikas; Datta, Ashim
ABSTRACT: A deficiency of zinc (Zn) is ubiquitous causing threat of Zn malnutrition worldwide, especially, due to reliance on Zn-poor cereal-based diets. As a principal staple grain, wheat ( Triticum aestivum L.) is consumed by 40% of global population. The wide gap between the available Zn concentration in wheat grain (20–35 mg kg −1 ) and that required Zn for human health (45 mg kg −1 ), urges the need for biofortification. Agronomic biofortification is a feasible and economic intervention strategy for mitigation of Zn deficiency or malnutrition by increasing Zn concentration and bioavailability in edible parts of cereals with increased yield; though there are bottlenecks at the root-shoot barrier and in grain filling. This review explores the reasons to enhance grain Zn bioavailability, and the role of fertilizer management on agronomic biofortification of wheat with Zn. Foliar, or soil + foliar application of Zn salts can increase the Zn concentration ≤60 mg kg −1 in whole wheat grain. The Zn-nanocarrier (Zn-Chitosan Nanoparticles) has higher Zn-use efficiency, than zinc sulfate. Grain Zn accumulation is regulated by Zn remobilization from shoot and continuous uptake during the grain filling of wheat. Foliar Zn application early during grain filling improves Zn transport in the endosperm, which is the main consumable grain fraction. Relevantly, newer-released cultivars exhibit Zn-Fe antagonism, may challenge a combined loading of Zn and Fe in cereal grains, but biofortification does not intend a trade-off between two. Consequently, the efficacy of Zn-biofortification needs to be studied using distinct biomarkers.